Kontemporäre Bildung Zu einem zeitgemäßen Verständnis von Bildung und Medien - Grünberger, Nina (innsbruck university press, 2017)
Who are we? Acceleration, change, contingency, digitality and technologisation raise the question of a con-tempory understanding of education and future-oriented educational concepts. Education must be thought along the historical course - that is, with time, contemporary. A contribution to this is made here by formulating socio-cultural implications for a contemporary understanding of education. This is done through a comprehensive examination of postmodern social diagnoses and a subsequent analysis of central educational theories. The ubiquity of digital technologies in the world we live in, and the crisis-prone nature of the present, must be addressed. This leads to a call to rethink previous understandings of education.